Pembenahan Pencatatan dan Pelaporan Keuangan Sanggar Rangkiang Salayo dengan menggunakan Program Akuntansi berbasis Excel - Verni Juita; Fitriyeni Oktavia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Sanggar Rangkiang Salayo is a women's business group in Solok, West Sumatra. It has been developing a knitting business. The business program focuses on improving product quality, innovation, and systematic business administration. One of the essential aspects of business administration is having good and proper financial records and reporting. Several activities have been carried out to improve the recording and reporting of their business finances using an Excel-based accounting program. In this activity, participants were given training and accompanied when practising each financial recording and reporting stage using a pre-designed accounting program. The method used in this activity was providing material through lectures and training using Excel-based accounting programs demonstrated in front of the training participants. This Excel-based accounting program was designed according to Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM), which consists of six working papers integrated. The results of this activity were members of the Rangkiang Salayo who were more skilled in recording and reporting financial transactions for their business.